Remarkable non-linear optical properties of gold cluster doped graphyne (GY): A DFT study - Rasool, Alvina; Zahid, Saba; Alfryyan, Nada; Ayub, Ali Raza; Ayub, Khurshid; Akhter, Mohammed Salim; Iqbal, Javed; Al-Buriahi, M.S.; Yousef, El Sayed (Journal of Molecular Graphics and Modelling, 2022)
The nonlinear optical (NLO) properties of gold (Au) doped graphyne (GY) complexes are the subject of this quantum mechanical investigation. Detailed profiling of GY@Aucenter, GY@Auside, GY@2Auabove,GY@2Auperpendicular, and GY@3Aucenter is accomplished at CAM-B3LYP/LANL2DZ. The differential influence of various GY based complexes on molecular geometry, vertical ionization energy (VIE), interaction energy (Eint), frontier molecular orbitals (FMOs), density of states (DOS), absorption maximum (λmax), molecular electrostatic potential (MEP), electron density distribution map (EDDM), transition density matrix (TDM), dipole moment (μ) and non-linear optical (NLO) properties have been investigated. Non-covalent interaction (NCI) analysis has been done to explore the sort of interactions in designed complexes. The vibrational frequencies are probed via infrared (IR) analysis. Doping tactics in all complexes dramatically changed charge carrier properties, such as shrinking band gap (Eg) and increasing λmax in the range of 3.97–5.58 eV and 288–562 nm respectively, compared to pure GY with 5.78 eV Eg and 265 nm λmax. When compared to GY (αO = 281.54 andβO = 0.21 au), GY@3Aucenter exhibited a significant increase in static mean polarizability (αO = 415 au) and the mean first hyperpolarizability (βo = 3652 au) attributable to its lowest excitation energy (ΔE). GY doping has been discovered to be advantageous for designing potential nanoscale devices by focusing on the symphony between small Au clusters and GY and their impacts on NLO aspects. [Display omitted] •Theoretical study of five Au doped GY complexes (GY@Aucenter – GY@3Aucenter) for nonlinear optical response.•Significant reduction of HOMO-LUMO gap and escalated linear polarizability (αO) and first hyperpolarizability (βO).•Au single and multi-doping is a selective strategy for enhancing the NLO properties of Graphyne (GY).